Multi-scale variability in tropical soil nutrients following land-cover change - Holmes, Karen W.; Roberts, Dar A.; Kyriakidis, Phaedon; Soares, João Vianei; Chadwick, Oliver A. (My University, 2005)
The effects of land-cover change on soil properties have reached regional proportions in the southwestern Amazon, and can be detected in their patterns at the scale of hundreds of thousands of square kilometers. Spatial analysis of an extensive soil profile database revealed four nested spatial scales at which different patterns in soil properties occur: <3, <10, <68, and >68 km. The shortest scales account for the majority of the spatial variability in the biogeochemically important properties (phosphorus, nitrogen, organic carbon), while the longest scales explain the most for pedologic properties (pH, aluminum, percent clay and sand). The magnitude and sign of correlations among soil properties changed with scale, indicating major shifts in distribution and soil dynamics depending on the scale of observation and analysis. Precipitation, substrate composition, topography, and biological influences vary over large areas, leading to variable distribution of soil properties, and complicating the evaluation of the effect of deforestation on biogeochemical cycling. We modeled the relationships among scale-specific patterns in soil properties and the soil forming state factors to tease out the relative impact of changing land cover. Soil property short-scale variability corresponded with the distribution of land cover and terrain attributes, medium scale variation with geology and state soil map classifications, and long scale with geology and precipitation. The strength of these relationships may be partially attributable to the resolution of the maps used as proxies for the soil forming factors. Land-cover change has already left a discernable imprint on broad-scale soil nutrient patterns, although it is still not the dominant process. © Springer 2005.
Keywords: Geostatistics; Land-cover change; Scale; Soil nutrients; Spatial variability; Tropics